PROFIL KETERAMPILAN BERPIKIR KRITIS DAN KREATIF CALON GURU KIMIA PADA PERKULIAHAN BIOKIMIA - Andi Wahyudi (Chemistry Education Department of Education and Teaching Faculty, 2020)
Critical thinking and creative thinking are important dimension in teaching of 21st century to facing the challenges of the industrial revolution 4.0. The aim of this research was to analyze undergraduate preservice teachers’ critical and creative thinking skills on a biochemistry course. It was conducted using case study to analyse real circumstance that happened in biochemistry course. The instruments was observation sheet, test items of critical thinking skills, test items of creative thinking skills and questionnaires were used to determine the responses students towards learning activity. Participant was 30 undergraduate preservice chemistry teachers in 2015. The finding of this research showed that biochemistry course only emphasizes on critical thinking skills and not provided briefing creative thinking skills. This means that the biochemistry course has not showed students’ balance skills on critical and creative thinking skills. This study suggest that need further research to develop a biochemistry program who can improve students’ critical thinking and creative thinking.